Efficacy of allogenic bone block graft in maxillary alveolar ridge reconstruction: A systematic review - Aishwarya Ramkishan Purohit; Rajashri Abhay Kolte; Abhay Pandurang Kolte; Vrushali Nilesh Lathiya (Wolters Kluwer Medknow Publications, 2024)
Background: The purpose of this systematic review was to assess the efficiency of allogenic bone block grafts for maxillary alveolar ridge reconstruction. Materials and Methods: An electronic literature search was conducted using the PubMed, Cochrane Library, and Google Scholar databases. In addition, manual searching was done. Randomized controlled trials (RCTs) and prospective clinical trials (non-RCTs) up to December 2022, presenting the outcomes of allogenic bone blocks in maxillary alveolar ridge reconstruction, were identified. The rate of resorption, survival rate of implants, and formation of new bone following ridge augmentation were the outcome parameters. The quality assessment of the studies included was done using Joanna Briggs Institute Critical Appraisal Tool. Results: A total of 13 studies that matched the inclusion criteria were included. The average rate of bone resorption ranged from 0.2 to 29.2 mm, with an implant survival rate of 96.87% across the included investigations. On an average, 25.83 mm (18.6-33/mm) of new mature compact osseous tissue was discovered, including viable osteocytes in close contact with the remnant cancellous bone. Conclusion: According to the results of the current systematic review, using allogenic bone block graft for reconstruction of atrophic maxillae appears to be an effective and reliable bone substitute for reconstruction of atrophic maxillae.